Importance of Cardiac Magnetic Resonance in a Patient With Crohn's Disease–Associated Constrictive Pericarditis. Issue 9 (1st March 2016) - Barake, Walid; Vonder Muhll, Isabelle; Paterson, David Ian
Abstract : Supplemental Digital Content is available in the text.